TRENDS OF ROAD TRAFFIC INJURY IN BHAVNAGAR REGION - AN AUTOPSY BASED STUDY. (Journal of Forensic Medicine & Toxicology, 2023)
Vehicular accidents are a common cause of death in our city. Most of deaths occurs because of injuries sustained over head, chest, abdomen and limbs. This study helps in evaluating the profile of cases of road traffic injury and its influencing factors with proportions of injuries sustained on the body. Study was performed at mortuary complex of a tertiary care centre in Bhavnagar. Highest number of cases (41 cases), belongs to 3rd decade of life, accounting 23%. Male deaths resulted in 79.78% of total fatalities (142 cases). Married victims include 85.39% (152 cases). Cases belonging rural population is 70.79% (126 cases). Occupation wise most victims were labourers & farmers, accounting for 61.80% (110 cases). Most accidents occurred in month of October (22 cases), followed by February (20 cases). Head injuries found in 59.55% (106 cases).
Keywords: Vehicular Accidents; Road Traffic Accidents; Traffic Injuries; Road Safety